Экономическая культура населения современной Украины (по материалам экспертного опроса) - Ефременко, Т. (Социология: теория, методы, маркетинг, 2006)
The purpose of this paper is to present the data of the first in Ukraine sociological research on economic culture of the population conducted by the Department of Economic Sociology (IS NASU) in 2005. The author expounds the views of experts on the essence, forms of manifestation, and indicators of economic culture. One -dimen sional and multidimensional nature of economic culture has made it necessary to analyze both generalized integral characteristics and various dilemmas existing in mass consciousness of the present day Ukrainian society.